Generation Z Motivation to Visit Ubud Toursim Area - Ni Putu Sri Anggraeni; Yayu Indrawati; Nyoman Ariana (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
Ubud tourism area is a famous tourist destination in Bali. Ubud is visited by many tourists both foreign tourists and domestic tourists. The number of foreign tourists who come to Ubud does not discourage domestic tourists to enjoy the existing tourist attractions. In the visit of Indonesian tourists in Ubud, there is Generation Z who also visited various tourist attractions in the Ubud Tourism Area and enjoyed the products offered. As a generation that is in adolescence and productive traveling is certainly one way to fill free time in the midst of busy learning and work. The purpose of this study is to analyze the motivation of Generation Z to visit Ubud Tourism Area. This study uses a quantitative approach with a sample of 100 respondents . Sampling techniques in this study using purposive sampling and data collection through the dissemination of questionnaires and literature studies. Data analysis techniques using quantitative descriptive analysis using confirmatory factor analysis, with IBM SPSS Analysis tool 23 for Windows. The results showed that there are two driving factors that motivate Generation Z to visit the Ubud tourism area, namely relaxation and leisure and experiencing something new, while the pull factor that motivates Generation Z to visit is the tourist destination environment. The results of this study implicate the importance of maintaining the beauty of the natural environment and the environment around the Ubud Tourism Area, because Generation Z takes a high interest in natural tourist attractions as a means of their relaxation